Brain Injury Outcomes after Adjuvant Erythropoietin Neuroprotection for Moderate or Severe Neonatal Hypoxic-Ischemic Encephalopathy: A Report from the HEAL Trial - Wisnowski, Jessica L.; Monsell, Sarah E.; Bluml, Stefan; Goodman, Amy M.; Li, Yi; Comstock, Bryan A.; Heagerty, Patrick J.; Juul, Sandra E.; Wu, Yvonne W.; McKinstry, Robert C.; Mathur, Amit M. (Developmental neuroscience, 2024)
Abstract Introduction: Erythropoietin (Epo) is a putative neuroprotective therapy that did not improve overall outcomes in a phase 3 randomized controlled trial for neonates with moderate or severe hypoxic-ischemic encephalopathy (HIE). However, HIE is a heterogeneous disorder, and it remains to be determined whether Epo had beneficial effects on a subset of perinatal brain injuries. Methods: This study was a secondary analysis of neuroimaging data from the High-dose Erythropoietin for Asphyxia and Encephalopathy (HEAL) Trial, which was conducted from 2016 to 2021 at 17 sites involving 23 US academic medical centers. Participants were neonates >36 weeks’ gestation undergoing therapeutic hypothermia for moderate or severe HIE who received 5 doses of study drug (Epoetin alpha 1,000 U/kg/dose) or placebo in the first week of life. Treatment assignment was stratified by trial site and severity of encephalopathy. The primary outcome was the locus, pattern, and acuity of brain injury as determined by three independent readers using a validated HIE Magnetic Resonance Imaging (MRI) scoring system. Results: Of the 500 infants enrolled in HEAL, 470 (94%) had high quality MRI data obtained at a median of 4.9 days of age (IQR: 4.5–5.8). The incidence of injury to the deep gray nuclei, cortex, white matter, brainstem and cerebellum was similar between Epo and placebo groups. Likewise, the distribution of injury patterns was similar between groups. Among infants imaged at less than 8 days (n = 414), 94 (23%) evidenced only acute, 93 (22%) only subacute and 89 (21%) both acute and subacute injuries, with similar distribution across treatment groups. Conclusion: Adjuvant erythropoietin did not reduce the incidence of regional brain injury. Subacute brain injury was more common than previously reported, which has key implications for the development of adjuvant neuroprotective therapies for this population.